The Influence of Sense and Perception Risk Regarding Interest in Visiting New Ciputri - Febrian, Athfal; Yusup, Abdul (Primanomics : Jurnal Ekonomi & Bisnis, 2024)
This research aims to know, analyze, and explain Sense in Ciputri Baru. to know, analyze and explain the Perceived Risk regarding Ciputri Baru. To find out, analyze and explain your interest in visiting, visit the Citri Baru website. To find out and analyze and explain the relationship between Sense and Perception risks in New Cioutri. To find out, analyze and explain the relationship in a partial way of sensory influence on interest in visiting Ciputri Baru, and to find out the partial influence between perceived risk on interest in visiting Ciputri Baru. To find out the simultaneous influence between the influence of senses and risk perception on interest, visit Ciputri Baru. This study was conducted using a quantitative method with a descriptive and verification approach. The population in this study uses New Ciputri's Instagram followers of 737 followers. The sample used in this study is 246 using the Slovin formula. The analysis technique used in this study is path analysis using partial and simultaneous hypotheses. This research is assisted by an analysis tool in the form of SPSS software. Sensory variables have affected positively and significantly in a partial way for the interest of Ciputri Baru visits. The influence of risk variables has a significant influence on the interest of Visit Ciputri Baru. With sensory variables and simultaneous perception, risk has a significant influence on the interest of Visit New Ciputri.